Uvod u klasifikaciju verbalne magije i verbalna magija u zapisanoj usmenoj hrvatskoj tradicijiIntroduction to the Classification of Verbal Magic and Verbal Magic in the Recorded Croatian Oral Tradition - Vukelić, Deniver (Studia mythologica Slavica, 2014)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">In this paper the main topic are different species of verbal magical shapes in the written Croatian oral tradition. Primarily, there is definition of verbal magic through linguistic, ethnological and historical perspectives, so its different contexts could be cleared. Furthermore, the most frequent forms of the verbal magic are soberly defined – charms, spells and curses, which are later depicted in examples preserved in different historical sources, compilations of Croatian oral tradition, collected from different tellers or in secondary scientific literature.